Consumers and Halal Cosmetic Products: Halal Label, Life Style and Word of Mouth Communication - Pujiastuti, Heny; Afendi, Arief; Junusi, Rahman El; Mahardianto, Agus (Journal of Digital Marketing and Halal Industry, 2022)
The lifestyle of consumer behavior is growing very rapidly, especially with regard to the halal lifestyle. The purpose of this study was to test whether the halal label, lifestyle and word of mouth had an effect on purchasing decisions. The type of research used is quantitative research with multiple linear regression. The data in this study are primary data with 100 respondents from the State Islamic University of Walisongo, Semarang, who use Wardah halal cosmetic products. The sampling technique was carried out using the simple random sampling method. The results of this study indicate that the halal label and lifestyle variables have a positive and significant effect on purchasing decisions. Meanwhile, the word of mouth variable has no effect on purchasing decisions. The implications of this study provide an explanation that the use of halal cosmetic products is an option for the millennial generation (Gen-Z) in making a decision to purchase a beauty product.